Tuesday

March 31, 2015

March 31, 2015

Posted by **A.W.** on Friday, March 6, 2009 at 2:53pm.

- Algebra -
**Damon**, Friday, March 6, 2009 at 4:51pm10 x + 6 y = -14 yes

21 x - 6 y = 39 yes

add those two

31 x + 0 = 25

so

x = -25/31 yes

Now go back and use -25/31 in either of the original equations to get y

5 (-25/31) + 3 y = -7

3 y = 125/31 -7

3 y = (125-217)/31

y = - 92/3

**Answer this Question**

**Related Questions**

algebra - Solve by the elimination method. x+4y=45 -x+4y=27 please step by step

Math need by 9pm cst - Solve by elimination method. Please show step by step ...

math - Please solve the system with the elimination method. Explain each step as...

math - solve by the elimination method: 9x-9y=18 7y-3x=-8 please solve step by ...

Algebra help - f(x)=x^3-4x^2-x+4 How do I find the x-intercept for this? This is...

pre algebra - solve the equation step by step.list each step along with the ...

Algebra 1--Step-by-Step - Can someone show me how to solve these step-by-step? ...

ALGEBRA HELP - When solving the equation, what property was used to go from step...

algebra - Solve by substitution method 3x+8y=17 2x+y=14 please show step by step...

Math - Solve by elimination: 5x+7y=77 , 5x+3y=53 can you please help me out step...